Tussen kulturele traditie en verandering: de Bamileke-Tontine. Traditionele Basis, actuele functionering en sociale reglementering - Van Dievoet, Grietje; Verboven, Dirk (Afrika Focus, 1993)
The Bamileke of Cameroon are generally considered as one of Africa’s economically well-adapted people. One of the factors in this process is unmistakably the adaptation of traditional savings and credit associations (ROSCA, tontine, Ntshwa) to the needs of the market economy. The basic principle of a tontine is very simple: at set times, every member contributes a fixed sum of money, which is handed over to one of its members, until everyone has received this "tontine ". This enables each member to dispose of a relatively large amount of money, that can be used to various ends: agriculture, education, economic investments, trade or whatever. The Bamileke have, under demographic pressure, massively migrated to urban areas, where they developed the rural ROSCA into an original urban variant, the "bourse d’argent". This is an intermediate form between traditional tontines and western Exchange-systems, and is extremely well adapted to the new economic demands. However, the complex functioning and the principles underlying both traditional and recent savings and credit associations are well anchored in traditional social structures and cultural norms. And both give the Bamleke a distinctive advantage in endogenous development, industry, and especially trade. The western banking-system on the other hand does not succeed to give confidence, and remain to a large extent to-be-avoided foreign institutions. This situation makes tontines a preferable instrument in development policy, for they guarantee financial responsibility and personal involvement. KEY WORDS: informal financial sector (ROSCA, tontine), Cameroon, Bamileke, endogenous development strategies